ANALISIS STRATEGI PENGELOLAAN DAN PERAN LEMBAGA DALAM RANGKA KONSERVASI DANAU SENTANI JAYAPURA (Analyze of Management Strategy and Institution Participation In Concervation of Sentani Lake, Jayapura) - Auldry F. Walukow; D. Djokosetiyanto; . Kholil; Dedi Soedarma (Media Konservasi, 2008)
The Sentani Lake located at Jayapura regency which covered : east Sentani District, Sentani District, and West Sentani district. Other area located in Jayapura city. Sentani lake has 9630 ha area with 52 m depth and 72 m mean surface level. Some problem on Sentani lake are erotion, domestic waste and industrial waste which due to Cu and Zn concentration in these lake over standard of water quality. The strategy consist of management and institution responsibility, and lake institution is needed to develop lake sustainability . Analyze method by ISM (interpretative structural modeling) with institution fellowship, goal in lake management and management model programe as some input . According to expert judgment, the institution elements responsed to develop management model of Sentani lake are marine and fishing institution, Housing institution, local leader and local institution, environmental institution, landscape intitution, university, and tourisme institution. That elements is the fourth level. The fourth elements level become the main driver power and to effect on next sub element. Co-Management institution is proposed in this research.Key words: institution responsibility, co-management, ISM, driver power, Sentani Lak.